Effect of Phosphorus Fertilizer Application Timing and Dosage on the Growth and Yield of Snow Pea (Pisum sativum L.) - Dita Widianti; Widiwurjani Widiwurjani; Agus Sulistyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Snow pea (Pisum sativum L.) is a high-value vegetable crop with increasing market demand; however, its productivity remains relatively low due to suboptimal cultivation practices, particularly phosphorus (P) fertilization management. This study aimed to evaluate the effects of phosphorus fertilizer application timing and dosage on the growth and yield of the Taichung variety of snow pea. The experiment was conducted in Mojoroto Village, Pacet District, Mojokerto Regency, Indonesia, using a factorial Randomized Block Design (RBD) with two factors: phosphorus fertilizer application timing (at planting, 7 days after planting [DAP], and 14 DAP) and phosphorus fertilizer dosage (60, 80, 100, and 120 kg/ha). The results showed that the combination of phosphorus fertilizer applied at 100 kg/ha and 7 DAP produced the highest number of pods, pod weight per plant, and pod yield per hectare. Furthermore, phosphorus application at 7 DAP enhanced nutrient uptake efficiency during the early vegetative stage, while a dosage of 100 kg/ha significantly increased yield components, resulting in a pod weight of 99.72 g/plant. These findings indicate that optimizing both the timing and dosage of phosphorus fertilizer application can improve the productivity and yield quality of snow pea and provide a basis for technical fertilization recommendations for highland cultivation.